The Interface Between Inflammatory Mediators and MicroRNAs in Plasmodium vivax Severe Thrombocytopenia - Santos, Marina L. S.; Coimbra, Roney S.; Sousa, Tais N.; Guimarães, Luiz F. F.; Gomes, Matheus S.; Amaral, Laurence R.; Pereira, Dhelio B.; Fontes, Cor J. F.; Hawwari, Ibrahim; Franklin, Bernardo S.; Carvalho, Luzia H. (Frontiers in Cellular and Infection Microbiology, 2021)
Severe thrombocytopenia can be a determinant factor in the morbidity of Plasmodium vivax, the most widespread human malaria parasite. Although immune mechanisms may drive P. vivax-induced severe thrombocytopenia (PvST), the current data on the cytokine landscape in PvST is scarce and often conflicting. Here, we hypothesized that the analysis of the bidirectional circuit of inflammatory mediators and their regulatory miRNAs would lead to a better understanding of the mechanisms underlying PvST. For that, we combined Luminex proteomics, NanoString miRNA quantification, and machine learning to evaluate an extensive array of plasma mediators in uncomplicated P. vivax patients with different degrees of thrombocytopenia. Unsupervised clustering analysis identified a set of PvST-linked inflammatory (CXCL10, CCL4, and IL-18) and regulatory (IL-10, IL-1Ra, HGF) mediators. Among the mediators associated with PvST, IL-6 and IL-8 were critical to discriminate P. vivax subgroups, while CCL2 and IFN-γ from healthy controls. Supervised machine learning spotlighted IL-10 in P. vivax-mediated thrombocytopenia and provided evidence for a potential signaling route involving IL-8 and HGF. Finally, we identified a set of miRNAs capable of modulating these signaling pathways. In conclusion, the results place IL-10 and IL-8/HGF in the center of PvST and propose investigating these signaling pathways across the spectrum of malaria infections.